Development of Cam Impingement following Operative Fixation of Acetabular Fractures - Zacharias, Anthony J.; Muffly, Brian T.; Zuelzer, David A.; Jacobs, Cale A.; Wright, Raymond D.; Duncan, Stephen T. (The Journal of Hip Surgery, 2022)
The development of femoroacetabular impingement following acetabular fracture fixation is under-recognized. This study assessed radiographic changes of the hip joint after acetabular fracture fixation, and the clinical implications of associated radiographic changes. Institutional review of patients under age 40 who underwent acetabular fracture fixation from 2010 to 2016 with minimum 1-year radiographic follow-up was performed. Two independent evaluators compared immediate postoperative radiographs and those at final follow-up for basic radiographic parameters. Chi-squared test, Fisher's exact test, and two-tailed t-tests were used to compare those with and without cam lesion development. Two-hundred twenty-four hips were reviewed, with 55 hips (53 patients) meeting inclusion criteria (age = 29.2 years, 60% male, average follow-up = 2.1 years). Average α angle increased from 53.8 to 75.5 degrees postfixation (p < 0.001). Average immediate postoperative joint space was unchanged from that at follow-up (3.6 versus 3.6 mm, p = 0.90), and there was no association between joint space narrowing and cam lesion development. Forty-four hips had postoperative α angles of less than 65 degrees. At final follow-up, 26/44 hips (59.1%) had α angles of greater than 65 degrees. Lower body mass index was an independent risk factor for increase in α-angle (p < 0.05). Hip dislocation, acetabular fracture pattern, age, and joint space narrowing were not risk factors for the development of cam deformity. Two patients had undergone hip preservation procedures at the last follow-up. Our findings identify the development of primarily femoral-sided femoroacetabular impingement following acetabular fracture fixation and highlight the importance of prolonged postoperative follow-up for these patients. Providers should scrutinize radiographs in those with new-onset pain or poor satisfaction following acetabular fixation.
Keywords: acetabular fracture; femoroacetabular impingement; cam lesion; hip arthroscopy